Kynurenine diminishes the ischemia-induced histological and electrophysiological deficits in the rat hippocampus - Sas Katalin; Robotka Hermina; Rózsa Éva; Ágoston Márta; Szénási Gábor; Gigler Gábor; Marosi Máté Gábor; Kis Zsolt; Farkas Tamás; Vécsei László; Toldi József (2008)
The neuroprotective effect Of L-kynurenine sulfate (KYN), a precursor of kynurenic acid (KYNA, a selective N-methyl-D-aspartate receptor antagonist), was studied. KYN (300 mg/kg i.p., applied daily for 5 days) appreciably decreased the number of injured pyramidal cells from 1850 +/- 100/mm(2) to 1000 +/- 300/mm(2) (p<0.001) in the CA1 region of the hippocampus in the four-vessel occlusion (4VO)-induced ischemic adult rat brain. A parallel increase in the number of intact, surviving neurons was demonstrated. Post-treatment with KYN (applied immediately right after reperfusion) proved to be much less effective. In parallel with the histology, a protective effect of KYN on the functioning of the CA] region was observed: long-term potentiation was abolished in the 4VO animals, but its level and duration were restored by pretreatment with KYN. It is concluded that the administration of KYN elevates the KYNA concentration in the brain to neuroprotective levels, suggesting its potential clinical usefulness for the prevention of neuronal loss in neurodegenerative diseases. (C) 2008 Elsevier Inc. All rights reserved.